The Group-lending Model and Social Closure: Microcredit, Exclusion, and Health in Bangladesh (Journal of Health, Population and Nutrition, 2009)
According to social exclusion theory, health risks are positively associated with involuntary social, economic, political and cultural exclusion from society. In this paper, a social exclusion framework has been used, and available literature on microcredit in Bangladesh has been reviewed to explore the available evidence on associations among microcredit, exclusion, and health outcomes. The paper addresses the question of whether participation in group-lending reduces health inequities through promoting social inclusion. The group-lending model of microcredit is a development intervention in which small-scale credit for income-generation activities is provided to groups of individuals who do not have material collateral. The paper outlines four pathways through which microcredit can affect health status: financing care in the event of health emergencies; financing health inputs such as improved nutrition; as a platform for health education; and by increasing social capital through group meetings and mutual support. For many participants, the group-lending model of microcredit can mitigate exclusionary processes and lead to improvements in health for some; for others, it can worsen exclusionary processes which contribute to health disadvantage. Key words: Exclusion; Economic assistance; Health status; Group-lending model; Health equity; Microcredit; Social exclusion; Bangladesh doi: 10.3329/jhpn.v27i4.3398 J Health Popul Nutr 2009 Aug;27(4):518-527